2011
DOI: 10.1002/jpln.201000395
|View full text |Cite
|
Sign up to set email alerts
|

Iodine biofortification in tomato

Abstract: Iodine is an essential element in the human diet, and iodine deficiency is a significant health problem. No attempts to increase iodine content in plant-derived food (biofortification) have so far been particularly effective. We studied iodine uptake in tomato (Solanum lycopersicum L.) to evaluate whether it is possible to increase the iodine concentration in its fruits. Iodine translocation and storage inside tomato tissues were studied using radioactive iodine. Potassium iodide was also supplied at different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(90 citation statements)
references
References 30 publications
5
69
0
5
Order By: Relevance
“…Other biofortified crops mentioned in the literature included provitamin A-rich bananas and papaya, 14 as well as tomatoes enriched with folate 15 or iodine. 16 In our review, we also found that all biofortified products released so far for planting, distribution, and human consumption have been developed using only conventional plant breeding. This methodology is based on the fact that plants often present wide genetic variation in nutrient content, which breeding programs benefit from by selecting varieties with the highest concentration of essential nutrients in order to improve the nutritional value of these crops.…”
Section: Regulatory Overviewmentioning
confidence: 84%
“…Other biofortified crops mentioned in the literature included provitamin A-rich bananas and papaya, 14 as well as tomatoes enriched with folate 15 or iodine. 16 In our review, we also found that all biofortified products released so far for planting, distribution, and human consumption have been developed using only conventional plant breeding. This methodology is based on the fact that plants often present wide genetic variation in nutrient content, which breeding programs benefit from by selecting varieties with the highest concentration of essential nutrients in order to improve the nutritional value of these crops.…”
Section: Regulatory Overviewmentioning
confidence: 84%
“…The factors are iodine content in the soil, iodine content in the feed, nutrient consumption and physiological stage of animal As shown in Table 2, soil iodine content was 3.09 mg/kg. Iodine was not classified as essential mineral for plant, but 0.5-1 mg/kg iodine in the soil could stimulate the plant growth (Weng et al, 2008;Landini et al, 2011). Soil iodine content is toxic for plant if the content reaches 10 mg/kg (Umaly and Poel, 1970).…”
Section: Resultsmentioning
confidence: 99%
“…Iodine is not included in essential mineral for plant but 0.5-1 mg/kg iodine in the soil can stimulate forage growth (Weng et al, 2008;Landini et al, 2011). Iodine up to 10 mg/kg in the soil can be toxic for plant (Umaly and Poel, 1970).…”
Section: Introductionmentioning
confidence: 99%
“…En cambio, en las plantas marinas parece operar únicamente el mecanismo asociado al bombeo de protones (Weng et al, 2013). La posterior movilización del yodo de la raíz hacia los tallos y hojas ocurre por el xilema (Herret et al, 1962;Mackowiak y Grossl, 1999;Zhu et al, 2003;Kato et al, 2013) aunque al igual que ocurre con otros elementos parece ocurrir una redistribución posterior del yodo vía floema (Landini et al, 2011).…”
Section: (Figura 2)unclassified
“…By contrast, in marine plants it seems to operate only the mechanism associated to proton pump (Weng et al, 2013). Subsequent mobilization of iodine from the root to the stems and leaves occurs through the xylem (Herret et al, 1962;Mackowiak and Grossl, 1999;Zhu et al, 2003;Kato et al, 2013) but as it occurs with other elements seems to be a subsequent redistribution of iodine via phloem (Landini et al, 2011).…”
Section: (Figura 2)mentioning
confidence: 99%